Recognition of Acoustic Signals of Loaded Synchronous Motor Using FFT, MSAF-5 and LSVM - GLOWACZ, Adam (Archives of Acoustics, 2015)
An article discusses a system of recognition of acoustic signal of loaded synchronous motor. This software can recognize various types of incipient failures by means of analysis of acoustic signals. A proposed approach uses acoustic signals generated by loaded synchronous motor. A plan of study of acoustic signal of loaded synchronous motor is proposed. Studies includes following states: healthy loaded synchronous motor, loaded synchronous motor with shorted stator coil, loaded synchronous motor with shorted stator coil and broken coil, loaded synchronous motor with shorted stator coil and two broken coils. The methods such as: FFT, Method of selection of amplitudes of frequencies (MSAF-5), Linear Support Vector Machine were used to identify specific state of the motor. The proposed approach can keep high recognition rate and reduce the maintenance cost of synchronous motors.